The periodontal health status of postmenopausal women and its relationship to bone mineral density (Mustansiria Dental Journal, 2024)
The relationship between changes in postmenopausal women and periodontalcondition had been studied in many countries. It has been suggested that estrogendeficiency may play a role in periodontal disease following menopause. The aim ofthis study was to investigate the influence of postmenopausal alteration on the clinicalperiodontal parameters and teeth loss. In addition, to determine the relationshipbetween systemic bone mineral density and periodontal disease in postmenopausal.womenSixty Iraqi women in total were involved in this study, 20 women as a controlgroup of age (35-45) years and forty postmenopausal women divided into two.subgroups: groupl for age (50-60) years and group 2 of age (60-70) years:Questionnaire involved the following periodontal parametersPlaque index (PI), gingival index (GI), bleeding on probing (BOP), pocketdepth (PD), clinical attachment level (CAL). All these parameters were measured andtabulated according to redefined scores, or counts, and the data was analyzed.statistically- Fifteen of forty postmenopausal women, were examined using dual energy xray absorptiometry (DEXA) equipment to measure bone mineral density (BMD) inorder to determine the relationship between (BMD) and any of the above periodontalparameters. The means, Gl, BOP, PD and CAL were found to be significantly higher.)in the postmenopausal group than the control (P